Persepsi Pendidik terhadap Pembelajaran IPA secara Terpadu di SMP/MTs Kota Banda Aceh - Fajrina Humayra*; Sulastri Sulastri; Abdul Gani (Jurnal Pendidikan Sains Indonesia, 2022)
Based on the Curriculum 2013, science learning in junior high schools is provided in an integrated way. However, the quality of science learning in fact is not encouraging. This is evidenced by science learning achievement in Indonesia is categorized as still low based on National Examination. The recent studies found that teachers conducted integrated science matter separately. This approach requires the ability of teachers, whereas not all science teachers in SMP/MTs are prepared from science education. This research was conducted in Banda Aceh. The research objective is to identify the teacher's perspective regarding integrated science based on teacher knowledge. This research uses descriptive qualitative research with questionnaire and semi-structured interviews. Data collection was carried out by proportional stratified random sampling. Respondents in questionnaire filling were 105 science teachers and in the interview were 21 people. The data analysis techniques are data collection, data reduction, data display, and conclusion drawing. The results showed that based on the teacher's perspective on integrated science, there is a high awareness of creating an effective teaching and learning environment for students regardless of the out of scientific field that is not linear according to sarjana pendidikan IPA. Subject matter of teachers is relevant to understand the concepts in integrated science which are interconnected with each other which continues to be strengthened for professional development. In addition, integrated science teachers have the ability to explore their beliefs with actual practice when teaching and it means that the theoretical knowledge possessed by teachers can be applied